2014
DOI: 10.1186/1750-1326-9-26
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression changes consistent with neuroAIDS and impaired working memory in HIV-1 transgenic rats

Abstract: BackgroundA thorough investigation of the neurobiology of HIV-induced neuronal dysfunction and its evolving phenotype in the setting of viral suppression has been limited by the lack of validated small animal models to probe the effects of concomitant low level expression of multiple HIV-1 products in disease-relevant cells in the CNS.ResultsWe report the results of gene expression profiling of the hippocampus of HIV-1 Tg rats, a rodent model of HIV infection in which multiple HIV-1 proteins are expressed unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
62
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 132 publications
(145 reference statements)
7
62
2
Order By: Relevance
“…In the studies reported here, where the rats were exposed to nicotine at a slightly higher dose and for a longer duration, as well as to potentially additional stress from behavioral and motor testing, we observed that TNF-α, IL-1, and IL-6 gene expression levels were all increased by smoke exposure in HIV1Tg rat brains, whereas IL-6 gene expression was not increased by the exposures in F344 rat brains, suggesting the existence of a greater susceptibility to such exposures for the transgenic rat. This is consistent with our previous findings where increased proinflammatory responses were demonstrated both systemically and in brains from the transgenic versus the wild-type animals and with other studies that demonstrated the presence of increased astrocyte and microglial activation the brains of transgenic rats that were produced on a Sprague-Dawley rat background (Repunte-Canonigo et al 2014). Also, analysis of peripheral blood immune cell phenotypes in HIV1Tg rats showed increased numbers of circulating cytotoxic T cells as well as increased percentages of helper T cells and monocytes as compared to F344 rats (Abbondanzo and Chang 2014), although helper T cells and monocytes can be functionally either proinflammatory or anti-inflammatory (Geissmann et al 2008).…”
Section: Discussionsupporting
confidence: 93%
“…In the studies reported here, where the rats were exposed to nicotine at a slightly higher dose and for a longer duration, as well as to potentially additional stress from behavioral and motor testing, we observed that TNF-α, IL-1, and IL-6 gene expression levels were all increased by smoke exposure in HIV1Tg rat brains, whereas IL-6 gene expression was not increased by the exposures in F344 rat brains, suggesting the existence of a greater susceptibility to such exposures for the transgenic rat. This is consistent with our previous findings where increased proinflammatory responses were demonstrated both systemically and in brains from the transgenic versus the wild-type animals and with other studies that demonstrated the presence of increased astrocyte and microglial activation the brains of transgenic rats that were produced on a Sprague-Dawley rat background (Repunte-Canonigo et al 2014). Also, analysis of peripheral blood immune cell phenotypes in HIV1Tg rats showed increased numbers of circulating cytotoxic T cells as well as increased percentages of helper T cells and monocytes as compared to F344 rats (Abbondanzo and Chang 2014), although helper T cells and monocytes can be functionally either proinflammatory or anti-inflammatory (Geissmann et al 2008).…”
Section: Discussionsupporting
confidence: 93%
“…We’ve also previously described in vivo imaging findings in this animal model suggestive of neuropathology using both magnetic resonance imaging (MRI) and positron emission tomography (PET) (Lee et al, 2014a, Lentz et al, 2014). Although there have been previous meticulous studies examining certain aspects of brain pathology in this animal model (Repunte-Canonigo et al, 2014, Royal et al, 2012), the exact neuropathology with respect to age and whether viral proteins are expressed in the CSF have not been thoroughly characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Although rodents engage in species-typical exploratory behavior, like humans, they utilize cognitive information such as memory of locations recently visited to guide their behavior. The altered exploratory behavior in HIV-1Tg rats could reflect similar deficits in cognition (Repunte-Canonigo 2014) that underlies the decline in everyday functioning that defines HIV-associated mild neurocognitive disorder in human HIV patients.…”
Section: Behavioral Alterations In the Hiv-1tg Ratmentioning
confidence: 99%
“…In a more structured test environment, such as a T-maze, rats have a very strong tendency to alternate arm choices as they explore across trials. This spontaneous alternation behavior is significantly reduced in HIV-1Tg rats (Repunte-Canonigo 2014). …”
Section: Behavioral Alterations In the Hiv-1tg Ratmentioning
confidence: 99%
See 1 more Smart Citation